OCCUPATIONAL STRESS AMONG FEMALE ACADEMIC STAFF OF HIGHER EDUCATIONAL INSTITUTIONS (HEIs) OF SINDH (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This research paper aims to determine occupational stress among female academic staff of Higher education institutes of Sindh which is a province of Pakistan. For this purpose different public & private sectors were selected on random basis for the collection of data with the help of questionnaires using â€œLikert Scaleâ€ ranging from â€œStrongly Agree to Strongly Disagreeâ€. The targeted Participants were female Lecturers, Assistant professor, Associate professor and Professors, age group from 21 to 60. From the 250 targeted sample, 220 responses were reasonable which were considered. The results of the research shows that Administrative factors are highly correlated with Peer Relationship Factors then working environment factor, Peer stress can be managed when (HEIs) treated working staff fairly, encourage team work, properly rewarded, better promotions, high job security and choices of doing work. The limitation of this study is that its implications are only applicable to the Khairpur&Sukkur cities because of the limited time & budget resources.Â